The preoperative management of dabigatran and its specific antidote idarucizumab in patients with nonvalvular atrial fibrillation – case reports - Tomić, Milan (Archives of Pharmacy, 2020)
Dabigatran is a novel oral anticoagulant preferred due to its ease of use, favorable pharmacokinetics, decreased potential for drug–drug interactions, and the lack of monitoring requirements. With the growing use of dabigatran, it is important to highlight that dabigatran increases the risk of hemorrhage after some procedures. Therefore, when dabigatran is used before the elective or urgent procedures, it is necessary to compare the thromboembolic event risk with the relative risk of bleeding. Before the approval of a reversal agent, the lack of specific antidotes had been the major limitation against the widespread utilization of dabigatran. In October 2015, idarucizumab, a humanized monoclonal antigen-binding antibody fragment capable of reversing the anticoagulant activity of dabigatran, has been introduced into the market to be used in life-threatening bleeding or urgent surgery. In this manuscript, the preoperative management of dabigatran and the initial experience of using idarucizumab in a patient with nonvalvular atrial fibrillation were described. We propose that the option of dabigatran reversal needs to be considered in patients with nonvalvular atrial fibrillation. However, additional research is needed to define optimal perioperative management of dabigatran and other novel oral anticoagulants, especially in high bleeding risk patients, and to determine whether pre-procedure coagulation testing should be performed.